2010
DOI: 10.1039/b9nr00268e
|View full text |Cite
|
Sign up to set email alerts
|

Wall-to-wall stress induced in (6,5) semiconducting nanotubes by encapsulation in metallic outer tubes of different diameters: A resonance Raman study of individual C60-derived double-wall carbon nanotubes

Abstract: We measure resonant Raman scattering from 11 individual C 60 -derived double wall carbon nanotubes with inner semiconducting (6,5) tubes and outer metallic tubes. The Raman spectra show the radial breathing mode (RBM) of the inner and the outer tubes simultaneously in resonance with the same laser energy. We observe that an increase in the RBM frequency of the inner tubes is related to an increase in the RBM frequency of the outer tubes. The Raman spectra also contain a sharp G − feature that increases in freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(57 citation statements)
references
References 22 publications
2
52
1
2
Order By: Relevance
“…Villalpando-Paez et al [61] showed that the (6,5) inner tubes in a double-wall carbon nanotube (DWNT) show different behavior when surrounded by different (n, m) outer tubes. The extra effect of a substrate in this case is a broad and open issue for future research.…”
Section: Substrate Interaction On Bundled and Multiwalled Tubesmentioning
confidence: 99%
“…Villalpando-Paez et al [61] showed that the (6,5) inner tubes in a double-wall carbon nanotube (DWNT) show different behavior when surrounded by different (n, m) outer tubes. The extra effect of a substrate in this case is a broad and open issue for future research.…”
Section: Substrate Interaction On Bundled and Multiwalled Tubesmentioning
confidence: 99%
“…In figure 6 we plot together the frequencies of the TO G-mode of the inner tube measured on index-identified DWNT (blue symbols) and, on the other hand, the ones obtained on (6,5)@ SC DWNTs by Villalpando-Paez et al (red symbols) [19].…”
Section: The G Modes On the Basis Of The Results Established From Ramentioning
confidence: 99%
“…It must be emphasized that the index-assignment of the outer tubes of these later DWNTs, and then their δr values, was reexamined by comparing the experimental RBLMs of reference [19] with the results of the model presented in the previous subsection of this paper. A shift of the TO mode is observed in a large interlayer distance range.…”
Section: The G Modes On the Basis Of The Results Established From Ramentioning
confidence: 99%
“…Хотя ранее и было проведено изучение индиви-дуальных полупроводниковых ДУНТ расположенных на подложке [11][12][13], в этих работах структуру двустенных нанотрубок идентифицировали косвенным способом с 328…”
Section: Introductionunclassified
“…Хотя ранее и было проведено изучение индиви-дуальных полупроводниковых ДУНТ расположенных на подложке [11][12][13] (27,17). Спектры нормализованы по интенсивности G-моды для иллюстративных целей.…”
Section: Introductionunclassified